Clusters in social networks with incomplete information - Caridi, Délida Inés (2010)
We have developed a method to recognize communities in networks which lack of some information. It has been conceived to be applied to the problem of getting information about people who were disappeared in the Argentine Province of Tucuman during the period 1975-1983. © 2010 World Scientific Publishing Company.